2005
DOI: 10.1191/0269216305pm1048oa
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards, and wishes for, euthanasia in advanced cancer patients at a palliative medicine unit

Abstract: The wish to die in these patients does not seem to be constant. Rather, this wish is more appropriately seen as an ambivalent and fluctuating mental 'solution' for the future. Health care providers should be aware of this when responding to utterances regarding euthanasia/PAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
114
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 28 publications
4
114
1
4
Order By: Relevance
“…First, some patients saw their DhD as a "hypothetical possibility" under certain conditions for the future, when pain or emotional suffering would become unbearable. This supports earlier data, such as results from semistructured interviews in 18 cancer patients, in whom wishes for euthanasia and physician-assisted suicide were found to be hypothetical [5]. This may be interpreted as a coping strategy of keeping control [5].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…First, some patients saw their DhD as a "hypothetical possibility" under certain conditions for the future, when pain or emotional suffering would become unbearable. This supports earlier data, such as results from semistructured interviews in 18 cancer patients, in whom wishes for euthanasia and physician-assisted suicide were found to be hypothetical [5]. This may be interpreted as a coping strategy of keeping control [5].…”
Section: Discussionsupporting
confidence: 86%
“…This supports earlier data, such as results from semistructured interviews in 18 cancer patients, in whom wishes for euthanasia and physician-assisted suicide were found to be hypothetical [5]. This may be interpreted as a coping strategy of keeping control [5]. Therefore, the existing construct of an increased DhD may benefit from a further differentiation between "non-acute" and "acute."…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Physician assisted suicide (PAS) refers to the patient intentionally and wilfully ending his or her own life with the assistance of another party [3,6,9]. Furthermore, it is not an assisted death in case where the intention is the relief of symptoms and not to hasten a patient's death [6].…”
Section: Introductionmentioning
confidence: 99%
“…The manner in which the symptoms present themselves also matters; if symptoms are sudden, have high intensity, or are prolonged, this can greatly contribute to existential suffering, and effective control of physical symptoms may therefore act as a buffer against thoughts of death and death anxiety [33]. Previous findings also support the connection between anticipatory fear of suffering and the wish for to hasten death via euthanasia [34]. This study showed not only that suffering experienced at the present moment is used to justify euthanasia, but also that fear of future suffering is.…”
Section: Discussionmentioning
confidence: 82%